Microbiome Variation in an Intertidal Sea Anemone Across Latitudes and Symbiotic States - Morelan, Ian A.; Gaulke, Christopher A.; Sharpton, Thomas J.; Vega Thurber, Rebecca; Denver, Dee R. (Frontiers in Marine Science, 2019)
Many cnidarians form symbiotic relationships with brown dinoflagellate algae in the genus Symbiodinium. Bacteria are important to this symbiosis, with diverse functions such as providing nutrients to the symbiont and pathogen protection to the cnidarian. Disrupted bacterial communities are associated with thermally stressed cnidarians, which have a higher likelihood of expelling their symbionts, an event called bleaching. To better understand the association between thermal tolerance and bacterial community structure, we studied communities associated with an exceptionally thermal tolerant cnidarian, Anthopleura elegantissima. This intertidal symbiotic sea anemone is distributed from the subtropical waters of Baja California to subarctic Alaska, and experiences daily temperature fluctuations of up to 20ºC. It is also flexible in its symbioses, predominantly hosting Symbiodinium, but occasionally hosting the green algae Elliptochloris marina or existing without symbionts in an aposymbiotic state. We used 16S rRNA gene amplicon sequencing to characterize the natural variation of microbial communities associated with Anthopleura elegantissima in these three symbiotic states and across a latitudinal gradient. In this study, we identified a core microbiome, made up predominantly of taxa typically found in coastal seawater. We found that the communities associated with A. elegantissima were weakly linked to latitude. Diversity analyses revealed significantly higher species richness values for microbial communities associated with anemones hosting E. marina. Lastly the microbiome communities associated with different symbiotic states were compositionally distinct. Taken together, our results suggest that the structure of microbial communities associated with these temperate cnidarians is tightly linked to symbiotic state and weakly linked to other biogeographic phenomena.